Determinants Influencing the Prevalence of Stunting in Toddlers - Nur Husnul Khatimah; Dea Zara Avila (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stunting remains a significant public health issue with long-term effects on the growth and development of children, particularly in regions with limited access to health resources. Various factors such as economic status, parenting practices, and access to health facilities contribute to its prevalence. This study aims to analyze the determinants influencing stunting among children under five years old in Sambane Village, Langgudu District, Bima Regency. A cross-sectional approach was used with data collected from 50 respondents through questionnaires. Statistical analysis using the Chi-Square test was conducted to examine the relationship between independent variables—namely economic status, water source, toilet type, mother's body mass index (BMI), mother's education, mother's occupation, mother's age, child vaccination status, and frequency of posyandu visits—and the prevalence of stunting. The findings revealed that economic status (χ² = 36.11, p < 0.001), water source (χ² = 29.17, p < 0.001), toilet type (χ² = 34.38, p < 0.001), maternal education (χ² = 36.11, p < 0.001), and maternal occupation (χ² = 25.69, p < 0.001) were significantly associated with stunting. These results highlight that strengthening socioeconomic conditions and improving access to basic health facilities are critical strategies in stunting prevention efforts.